2017
DOI: 10.1063/1.4984955
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer graphene-insulator-semiconductor emitter for large-area electron lithography

Abstract: The rapid adoption of nanotechnology in fields as varied as semiconductors, energy, and medicine requires the continual improvement of nanopatterning tools. Lithography is central to this evolving nanotechnology landscape, but current production systems are subject to high costs, low throughput, or low resolution. Herein, we present a solution to these problems with the use of monolayer graphene in a graphene-insulator-semiconductor (GIS) electron emitter device for large-area electron lithography. Our GIS dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The transfer of graphene synthesized on Cu foil by thermal CVD appears to be best suited to the fabrication of a high-quality single-layer graphene electrode considering the above two points. There have been several reports on the electron emission from a GOS structure fabricated by transferring CVD graphene on the oxide layer from the Cu foil. However, their electron emission efficiencies were very far from the ideal values, that is, the reported maximum electron emission efficiency of the GOS structure fabricated by transferring single-layer graphene is 13% . This low value most likely resulted from contaminants at the interface between the graphene electrode and oxide layer from the transfer processes, which are the most critical electron scattering sources.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of graphene synthesized on Cu foil by thermal CVD appears to be best suited to the fabrication of a high-quality single-layer graphene electrode considering the above two points. There have been several reports on the electron emission from a GOS structure fabricated by transferring CVD graphene on the oxide layer from the Cu foil. However, their electron emission efficiencies were very far from the ideal values, that is, the reported maximum electron emission efficiency of the GOS structure fabricated by transferring single-layer graphene is 13% . This low value most likely resulted from contaminants at the interface between the graphene electrode and oxide layer from the transfer processes, which are the most critical electron scattering sources.…”
Section: Results and Discussionmentioning
confidence: 99%
“…54−57 However, their electron emission efficiencies were very far from the ideal values, that is, the reported maximum electron emission efficiency of the GOS structure fabricated by transferring single-layer graphene is 13%. 56 This low value most likely resulted from contaminants at the interface between the graphene electrode and oxide layer from the transfer processes, which are the most critical electron scattering sources. In addition, the transfer process is not suited to the mass production of GOS devices for future industrial applications.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…These excellent features of graphene suggest the ideal material for the gate electrode of the MOS type electron emission source. In fact, the efficiency of planar-type electron sources has been improved to 0.3~13 % by suppression of electron scattering using graphene gate electrode [27][28][29][30][31][32]. However, further improvement of the electron emission efficiency of the planar-type electron emission source has been required to obtain sufficient electron beam current from an emission area equivalent to the electron source sizes of the conventional electron guns.…”
mentioning
confidence: 99%
“…Later, with refined technologies, the properties of MIM/MOS cathodes were significantly improved [22,23], while the emission mechanism apparently came into agreement with the original concept [15]. The most recent progress was related to the idea of using graphene (G) films as top electrodes [24][25][26]; Murakami et al reported on the achievement of emission efficiency up to ~50% and current densities >100 mA/cm 2 with the GOS structures [26].…”
Section: Introductionmentioning
confidence: 95%